Epistemology of Science in Scientific Research - Yaumi Rohmah; Nur Afika Fitriani; Agung Winarno (Pusat Riset dan Inovasi Nasional, 2024)
Epistemology is a branch of philosophy known as the epistemology of science that focuses on basic questions about scientific knowledge, such as how knowledge is acquired, developed, and validated. The methods used in idea articles are useful for developing new ideas, critiquing existing theories, or providing new insights into the issues or problems being discussed. There are several reasons why people should study epistemology: first, strategic reasons because strategy is fundamental to achieving certain goals. Second, cultural reasons, because culture is part of knowledge and is important in every aspect of culture. Third, educational reasons, because education is a conscious effort to develop views of life, attitudes, and perspectives.